Evaluasi Proses Bisnis Manajemen Inventori Menggunakan Metode Quality Evaluation Framework (QEF) Pada Bidang Inventori PT. PJB UBJOM PLTU Paiton - Azri Putri Rahmatika; Nanang Yudi Setiawan; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Logistics field at PT. PJB UBJOM Paiton Power Plant oversees three other areas of the field of inventory, procurement, and warehouse. In the inventory field, there is a problem of not achieving the company's target in three business process areas from four areas owned by the inventory field. Based on self-assessment data for the third quarter of 2017, the three areas that have not met the target are cataloging, request order making and implementation policymaking. From these problems, it is necessary to evaluate the measurement of the problems that occur in the company, in order to know the factors that cause the unfulfilled targets. The Quality Evaluation Framework (QEF) method is used because it can find the gap between the target and the result of the calculation. Business processes that have been modeled using Business Process Management Notation (BPMN) will provide mapping results on the quality factors of each business process. After obtaining an inappropriate factor between the target and the calculation result from the calculation result, then the root problem analysis is done using Fault Tree Analysis (FTA). Analysis using FTA can help the company to find the root of the problems found from the problems obtained based on the evaluation results. The advantage of using the FTA method is to identify the relationship between the causes of the problems found. The result of this research is finding 4 factors of evaluation result with QEF method which is not in accordance with target based on the calculation result. And the discovery of 12 root problems from the analysis based on the four factors of the evaluation results.